Genetic Potential of Local Rice Germplasm Specific Tidal Swamps of South Sumatra: Potensi Genetik Plasmanutfah Padi Lokal Spesifik Rawa Pasang Surut Sumatera Selatan - Annisa; N.W. Sariningtias; J. Amirullah; N.P. Sri Ratmini; Yustisia (Program Studi Agribisnis Universitas Sumatera Selatan, 2021)
The potential for sub-optimal tidal land can be increased by using new adaptive rice varieties, both under conditions of existing constraints (low pH, high Fe) and conditions affected by global climate change (increased temperature, pest and diseases attacks, floods, droughts). The genetic material needed to create new adaptive superior varieties (NSV) is rice genetic resources (SDGs) which have been tested to be tolerant of various constraints. Information on tidal rice SDG has been obtained from the identification results in South Sumatra. This information can be explored and utilized by breeders to create rice NSV. The diversity and potential of the resulting NSV can provide many alternatives for users in choosing NSV according to their conditions and preferences. Specific characteristics of tidal local rice genetic resources that have been identified are the age of harvest, resistance to environmental stresses (low pH, immersion), resistance to pests and diseases, panicle character, and rice texture. The results of the NSV breeding program can be disseminated and implemented, among others, in increasing the cropping index (shortage), the anticipation of global climate change (pest/disease resistant, soaking resistant), and specification of development areas according to consumer preferences (rice texture). The implementation of this effort requires coordination and synchronization between related institutions and is expected to impact increasing national rice production and food security